Psihoanalitička interpretacija parapsiholoških pojava - Jančić, Srdjan (Monitor ISH, 2005)
The psychoanalytical interpretation of parapsychological phenomena: a semiological approach. The paper deals with the approach of psychoanalysis to the so-called parapsychological phenomena. Illustrated by several examples of these phenomena, which have been interpreted and used bz psychoanalysts to support their premises, the problem of interpretation is transferred to a semiological framework to reveal the difficulties and inadequacies of the psychoanalytical approach. The analysis seeks to show how semiology may help reformulate the problems which emerge in interpreting the so-called parapsychological experiences.
Keywords: psihoanaliza; parapsihološki pojavi; interpretacija; semiologija